Nanostructured Carbon-Doped BN for CO2 Capture Applications - Rimeh Mighri; Kevin Turani-I-Belloto; Umit B. Demirci; Johan G. Alauzun (Nanomaterials, 2023)
Carbon-doped boron nitride (denoted by BN/C) was prepared through the pyrolysis at 1100 °C of a nanostructured mixture of an alkyl amine borane adduct and ammonia borane. The alkyl amine borane adduct acts as a soft template to obtain nanospheres. This bottom-up approach for the synthesis of nanostructured BN/C is relatively simple and compelling. It allows the structure obtained during the emulsion process to be kept. The final BN/C materials are microporous, with interconnected pores in the nanometer range (0.8 nm), a large specific surface area of up to 767 m2·g−1 and a pore volume of 0.32 cm3·g−1. The gas sorption studied with CO2 demonstrated an appealing uptake of 3.43 mmol·g−1 at 0 °C, a high CO2/N2 selectivity (21) and 99% recyclability after up to five adsorption–desorption cycles.